Master track of POLARSTERN cruise PS148 in 1 sec resolution (zipped, 112 MB) - Dannheim, Jennifer (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2025)
Raw data acquired by position sensors on board RV Polarstern during expedition PS148 was processed to receive a validated master track which can be used as reference of further expedition data. During PS148 two Trimble Marine R750 GPS receivers and the iXBlue HYDRINS hydrographic survey inertial navigation system were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.awi.de) with a resolution of 1 sec. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.
Keywords: 1 sec resolution